Educating dengue hemorrhagic fever to Jumantik Cadres using mobile application for mosquito nest eradication - Kholis Ernawati; Indah Kurnianingsih; Nurmaya Nurmaya; Muhamad Fathurahman; Muchamad Rinaldy; Keysha Farach Dwikhanza; Putri Alfira; Salsabila Azmi Qatrunnada; Rifda Wulansari (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Dengue Haemorrhagic Fever (DHF) cases are rising due to community efforts to eliminate mosquito nests. This impacts how people act. Community educators known as "Jumantik cadres" are using the YARSI University DHF Counseling Mobile Application. This app was created by YARSI University researchers in 2019-2020 and was introduced in Ciseeng village on July 29, 2021. Fifteen cadres learned to use it both online and offline. They were tested with surveys about DHF knowledge. Results showed limited understanding after using the app (e.g. only 13.3% understood headaches, 40% knew about nausea). Interviews also helped understand app use. Interestingly, 40% knew about the Aedes aegypti mosquito's life cycle. Some wrong ideas persisted (26.7% thought birds' drinking spots couldn't breed mosquitoes, and 53.3% understood mosquito bites). The YARSI app was liked for being easy to use. It helps Jumantik cadres educate and increase awareness about DHF. By using this app, they can share knowledge and fight against DHF more effectively.